2003
DOI: 10.1038/sj.leu.2402969
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR identifies a minimal deleted region of 120 kb extending from the Philadelphia chromosome ABL translocation breakpoint in chronic myeloid leukemia with poor outcome

Abstract: Fluorescence in situ hybridization (FISH) analysis has shown previously that 10-15% of chronic myeloid leukemias (CML) have hemizygous deletions of variable sizes affecting regions that flank the ABL and BCR translocation breakpoints on the derivative chromosome 9, and these patients have a poor outcome. FISH studies using large commercial genomic probes have previously suggested that haploinsufficiency of sequences flanking either ABL or BCR modify the disease process of CML and lead to an unfavorable prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…resulting in variable deletions size as a consequence of a nonrecurrent event (Sinclair et al, 2000;Storlazzi et al, 2002;Kolomietz et al, 2003;Fourouclas et al, 2006;Kreil et al, 2007). The deletions on der(9) have been associated with an adverse prognosis in relation to the efficacy of interferon-a therapy, whereas controversial data are available about their influence on the response to imatinib.…”
Section: Segmental Duplications In CML F Albano Et Almentioning
confidence: 99%
“…resulting in variable deletions size as a consequence of a nonrecurrent event (Sinclair et al, 2000;Storlazzi et al, 2002;Kolomietz et al, 2003;Fourouclas et al, 2006;Kreil et al, 2007). The deletions on der(9) have been associated with an adverse prognosis in relation to the efficacy of interferon-a therapy, whereas controversial data are available about their influence on the response to imatinib.…”
Section: Segmental Duplications In CML F Albano Et Almentioning
confidence: 99%
“…8,27 Such submicroscopic deletions, below the level of detection by FISH, have been identified in a small series of patients whose prognosis was poor. 9 A candidate tumour suppressor gene, PRDM12, was identified in these cases 32 and subsequently shown to be deleted in a case of Ph-positive CML with a variant translocation. 33 No association with survival has yet been established for deletions of der(9) in ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including our laboratory, have investigated this marker on CLL B cells and found that greater than 30% CD38 expression within a CLL leukemic population correlates to an overall shorter time to progression and, in general, a poor clinical outcome. [1][2][3][4][5] However, another study suggests that scoring CLL B-cell CD38 expression using both percent-positive and mean fluorescence intensity (MFI) is a more accurate prognostic tool for B-CLL patients. 6 Recently, Ghia et al 7 found that even a small distinct population of CD38 pos cells, displayed as a small peak in a bimodal CD38-staining profile, was associated with progressive disease.…”
Section: Figurementioning
confidence: 99%
“…2 The PRMD12 gene warrants further attention in order to elucidate its role in the pathogenesis of CML.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation